Adipose transplantation improves olfactory function and neurogenesis via PKCα-involved lipid metabolism in Seipin Knockout mice - Yang, Jing (2023)
Background: Lipodystrophy-associated metabolic disorders caused by Seipin deficiency lead to not only severe lipodystrophy but also neurological disorders. However, the underlying mechanism of Seipin deficiency-induced neuropathy is not well elucidated, and the possible restorative strategy needs to be explored. Methods: In the present study, we used Seipin knockout (KO) mice, combined with transcriptome analysis, mass spectrometry imaging, neurobehavior test, and cellular and molecular assay to investigate the systemic lipid metabolic abnormalities in lipodystrophic mice model and their effects on adult neurogenesis in the subventricular zone (SVZ) and olfactory function. After subcutaneous adipose tissue (AT) transplantation, metabolic and neurological function was measured in Seipin KO mice to clarify whether restoring lipid metabolic homeostasis would improve neurobehavior. Results: It was found that Seipin KO mice presented the ectopic accumulation of lipids in the lateral ventricle, accompanied by decreased neurogenesis in adult SVZ, diminished new neuron formation in the olfactory bulb, and impaired olfactory-related memory. Transcriptome analysis showed that the differentially expressed genes (DEGs) in SVZ of adult Seipin KO mice were significantly enriched in lipid metabolism. Mass spectrometry imaging showed that the levels of glycerophospholipid and diglyceride (DG) were significantly increased. Furthermore, we found that AT transplantation rescued the abnormality of peripheral metabolism in Seipin KO mice and ameliorated the ectopic lipid accumulation, concomitant with restoration of the SVZ neurogenesis and olfactory function. Mechanistically, PKCα expression was up-regulated in SVZ tissues of Seipin KO mice, which may be a potential mediator between lipid dysregulation and neurological disorder. DG analogue (Dic8) can up-regulate PKCα and inhibit the proliferation and differentiation of neural stem cells (NSCs) in vitro, while PKCα inhibitor can block this effect. Conclusion: This study demonstrates that Seipin deficiency can lead to systemic lipid disorder with concomitant SVZ neurogenesis and impaired olfactory memory. However, AT restores lipid homeostasis and neurogenesis. PKCα is a key mediator mediating Seipin KO-induced abnormal lipid metabolism and impaired neurogenesis in the SVZ, and inhibition of PKCα can restore the impaired neurogenesis. This work reveals the underlying mechanism of Seipin deficiency-induced neurological dysfunction and provides new ideas for the treatment of neurological dysfunction caused by metabolic disorders.